แบบจำลองการอธิบายความเจ็บป่วยต่อความร่วมมือในการใช้ยาของผู้ป่วยโรคหืดในศูนย์บริการสาธารณสุขเทศบาลเมืองลำพูน - พงษ์นรินทร์ จินดา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Explanatory model can be used to explain the disease and illness which related to health belief, and experience, which related to social and culture. The aims of this study were 1) To study the medication adherence in asthmatic patients 2) To determine the explanatory model on medication adherence in asthmatic patients 3) To compare explanatory model on medication adherence between controlled asthmatic group and uncontrolled asthmatic group. Data were collected from 16 asthmatic patients at Lamphun Municipal Public Health Center by in-depth interview and non-participatory observation during November2013 to January 2014. The results demonstrated that most asthmatic patients were good adherence of oral form and inhaled form of bronchodilator. In contrast, the adherence of inhaled corticosteroid, the most effective medication for long-term management of asthma, was poor. Moreover, we also found that patients who had good medication adherence were controlled asthmatic group while patients with poor medication adherence were uncontrolled asthmatic group. According to 5 dimensions explanatory model consist of etiology, timing and symptom of disease, pathophysiology of disease, severity and complication of disease and treatment, patients’ perspective of disease etiology, timing and symptom of disease, and pathophysiology of the disease were not different between groups, which adherence and controlled asthmatic patients group and non-adherence and uncontrolled asthmatic patient group. Patients in both groups realized that the etiology of asthma caused by inhalation of pollution and allergen from their work environment and daily life. They also know that the symptoms of asthma occur during patient receiving triggered substances, and pathophysiology of disease was upper respiratory tract related to abnormal symptoms when asthma exacerbation. They perceived based on experiences of illness and believe. Conversely, patients’ perspective of severity of the disease and treatment were not different between both of asthmatic groups, in which adherence and controlled asthmatic patients considered asthma as a chronic disease which need continuous treatment with inhaled corticosteroid to control the disease. Whereas, non-adherence and uncontrolled asthmatic patients believed that asthma is an acute disease which needs treatment only when the symptoms occur. In conclusion, patients’ perspective of severity of disease and treatment in explanatory model could predict the medication adherence and success treatment in asthmatic patients at Lamphun Municipal Public Health Center.